FEATURES OF THE MORPHLOLOGIC COMPOSITION OF BLOOD OF TURKEYS - Rebezov, Yaroslav; Gorelik, Olga; Rebezov, Maksim; Nikolaeva, Ludmila; Shcherbakov, Pavel; Dashkin, Askhat; Bezhinar, Tatyana; Bobyleva, Irina; Shcherbakova, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
Blood morphology is most commonly used to assess the clinical status of birds. The purpose of the work is to study the morphological characteristics of the blood of turkeys of the Broad-Breasted White and Hybrid breeds of different crosses, and their dynamics depending on age. It has been established that morphological and biochemical blood parameters varying within the standard limits during growing in industrial conditions. At the same time the value of blood parameters depends on the age and genotype of the bird, determined both by the breed and the cross. Thus, the number of erythrocytes (by 17.88-20.47%), hemoglobin (by 18.32-40.52%) and ESR (by 26.76-50.25%) increases in the blood of turkeys during their growth, indicating the level of respiratory gas need in life processes and the kinetic stability of red cells. At the same time, the ratio between erythrocytes and hemoglobin, estimated by the size of MGC and color index, has the most optimal value in turkeys of the middle cross Hybrid Grade Maker (Group III) and heavy cross Hybrid Converter (Group IV), which determines the rate of metabolic processes in their organism, interacting with the level of oxygenation. The level of white blood cell count depends on age and cross. According to this indicator birds of medium (group I) and heavy cross of Broad-Breasted White are superior to individuals of medium cross of Hybrid Grade Maker (group III) and heavy cross of Hybrid Converter (group IV) by 3.04-14.47% depending on their age.